2019
DOI: 10.1530/eje-19-0291
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitors and type 1 diabetes mellitus: a case report and systematic review

Abstract: Objective To better define the rare adverse event (AE) of diabetes mellitus associated with immune checkpoint inhibitors (ICIs). Design and methods We report the case of a lung cancer patient with diabetic ketoacidosis (DKA) and autoimmune thyroiditis during pembrolizumab treatment. We provide a systematic review of all published cases (PubMed/Web of Science/Cochrane, through November 2018) of autoimmune diabetes mellitus related to blockade of the cytotoxic T-lymphocyte antigen 4 (CTLA-4)-, programmed cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
217
4
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(240 citation statements)
references
References 119 publications
12
217
4
7
Order By: Relevance
“…Although new-onset DM had not been reported in clinical trials involving CTLA-4 inhibitors, it had been reported in <1% of patients included clinical trials on PD-1 inhibitors, with higher rates (up to 1.5%) being observed with the combined use of CTLA-4 and PD-1 inhibitors ( 87 ). The latest review identified 91 case reports of ICI-related DM from the literature ( 88 ). Many cases of DM following ICI therapy were reported in 2016 and 2017, after anti-PD-1 antibodies had been approved in 2014 ( 2 ).…”
Section: Immune Checkpoint Inhibitor-related Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…Although new-onset DM had not been reported in clinical trials involving CTLA-4 inhibitors, it had been reported in <1% of patients included clinical trials on PD-1 inhibitors, with higher rates (up to 1.5%) being observed with the combined use of CTLA-4 and PD-1 inhibitors ( 87 ). The latest review identified 91 case reports of ICI-related DM from the literature ( 88 ). Many cases of DM following ICI therapy were reported in 2016 and 2017, after anti-PD-1 antibodies had been approved in 2014 ( 2 ).…”
Section: Immune Checkpoint Inhibitor-related Diabetes Mellitusmentioning
confidence: 99%
“…Importantly, most of the cases with ICI-induced DM on ipilimumab received anti-PD-1 and/or interferon pretreatment ( 91 , 92 ). The main tumor types among patients who developed DM included melanoma (53%) and NSCLC (15%) ( 88 ).…”
Section: Immune Checkpoint Inhibitor-related Diabetes Mellitusmentioning
confidence: 99%
“…PD-1/PD-L1 related autoimmune diabetes (type 1 diabetes mellitus, T1DM) were rare with an incidence of 1% ~53% of which had at least one positive islet autoantibody ( 57 ) and 21% had two or more ( 58 ). A Hispanic boy with insulin autoantibody and islet antigen 2 antibody-positive, was reported to suffer from T1DM which presented with acute progression to hyperglycemia and diabetic ketoacidosis after treated with pembrolizumab because of the progression of classical Hodgkin lymphoma ( 59 ).…”
Section: Predictive Biomarkers For Pd-1/pd-l1 Inhibitors-related Toximentioning
confidence: 99%
“…Autoimmune diabetes mellitus (DM) is a rare complication (<1%) [44] [30]. The time to onset of hyperglycemia varies from the first weeks to 12 months after starting ICIs [45;46].…”
Section: Endocrine Immune-related Adverse Eventsmentioning
confidence: 99%
“…A characteristic feature is a very rapid increase in glycemia with complete lack of insulin secretion, confirmed by undetectable C-peptide levels at the time of diagnosis. Patients often present with signs and symptoms of hyperglycemia or ketoacidosis [44]. Glucose levels should be routinely checked during the course of immunotherapy.…”
Section: Endocrine Immune-related Adverse Eventsmentioning
confidence: 99%